2013
DOI: 10.5001/omj.2013.30
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extended-spectrum β-Lactamases-producing Escherichia coli from Hospitals in Khartoum State, Sudan

Abstract: The prevalence of ESBL-producing E. coli detected in this study is of great concern, which requires sound infection control measures including antimicrobial management and detection of ESBL-producing isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
25
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 16 publications
10
25
5
Order By: Relevance
“…Moreover, our finding revealed a high frequency of ESBL-producing Enterobacteriaceae, such as Proteus mirabilis and Enterobacter cloacae ( Table 2). A previous study at Khartoum state hospitals found that ESBL producer was 30.2% among E. coli [26]. A similar observation has been documented elsewhere [17].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, our finding revealed a high frequency of ESBL-producing Enterobacteriaceae, such as Proteus mirabilis and Enterobacter cloacae ( Table 2). A previous study at Khartoum state hospitals found that ESBL producer was 30.2% among E. coli [26]. A similar observation has been documented elsewhere [17].…”
Section: Discussionsupporting
confidence: 82%
“…This study showed that 17% of B. cereus, 8% C. freundii, 21% E. coli, 10% K. pneumoniae, 17% M. morganii, 9% P. aeruginosa, 6% P. mirabilis, 7% S. aureus and 5% Serratia marcecens isolates were ESBL-producing isolates in the salad vegetables. The prevalence of ESBLsproducing bacteria in this study was similar to that recorded in other developing countries such as Khartoum Teaching Hospital, Sudan (45.1%) [33], and in Lebanon (15.4%) [34]. K. pneumoniae and E. coli are the most common species producing ESBLs in this study.…”
Section: Discussionsupporting
confidence: 87%
“…In the hospital environment, under selection pressure, plasmids could be transferred between the patients and hospital personnel by hands (11,24). The possible explanation for this observation is the fact that ESBLs are encoded on plasmids and therefore could be easily transmitted as resistance gene elements for other antimicrobials, as well as from one organism to another (25).…”
Section: Discussionmentioning
confidence: 99%
“…There are many risk factors for colonization or infection with ESBL-producing isolates, such as long-term antibiotic exposure, prolonged intensive care unit stay, nursing home residency, severe illness, residence in an institution with frequent use of ceftazidime and other third-generation cephalosporin, and instrumentation or catheterization (25). Correct use of sterile gloves and systematic hand decontamination before and after visiting the patients and visitors' restriction are some of isolation measures (26).…”
Section: Discussionmentioning
confidence: 99%